BindingDB Entry 50038879: Protein tyrosine phosphatase 1B inhibitory effects of depsidone and pseudodepsidone metabolites from the Antarctic lichen Stereocaulon alpinum. - BindingDB (BindingDB, 2012)
Small molecule binding data for protein Protein-tyrosine phosphatase 1B, Uniprot P18031